Lowest eigenvalues of the Dirac operator for two color QCD at finite density - Bittner, Elmar; Lombardo, Maria Paola; Markum, Harald; Pullirsch, Rainer (Arxiv, 2001)
We investigate the eigenvalue spectrum of the staggered Dirac matrix in full QCD with two colors and finite chemical potential. Along the strong-coupling axis up to the temperature phase transition, the low-lying Dirac spectrum is well described by random matrix theory (RMT) and exhibits universal behavior. The situation is discussed in the chirally symmetric phase and no universality is seen for the microscopic spectral density.
Gesehen am 11.10.2022